The bus stop - Chong, Rebecca (2018)
I wanted to create a film that resonates with people’s experiences and feelings about waiting, hoping in vain, and being fixated on the past. I was determined to portray the idea that it is possible for one to overcome one’s own mental and emotional barriers, and to move on in life. I wanted to inspire people to let go of their sadness, their past, and move on courageously in life. I achieved these objectives of my film through effective storytelling where I employed visual metaphors—the circular bus stop sign which shows my character looking into her memories, being taken back into her past in full circle. I wanted to illustrate the idea that one’s past, present, and future are all part of one’s life cycle, that one always visits one’s memories, and at times, live in the present moment, and at other times ponder about the future, and the cycle repeats in full circle. Another approach that I adopted was to utilise paper as a medium instead of just merely drawing out my film (in 2 Dimensional (2D) ) as I was intrigued by the idea of letting my paper characters come to life. Just like how an inanimate object such as paper can come to life, my character’s memories (all done in paper) that seem distant and intangible, are actually very much alive, that one’s memories are still very much a part of one’s life. Along the way, I discovered that my project could be hard to relate to due to its metaphorical associations. Hence, I ensured that the circular motif recurs throughout the film so as to reiterate the idea of the nature of life as a full circle. My film is, perhaps, original in its way due to the idea and message behind the film— the metaphorical associations with life as a circle. Perhaps my film is not totally original but it has its own flavour where the film is shown in black and white, in a world devoid of colour and feeling, but slowly eases into colour (with the orange hue) to show that her memories come to life. It may be difficult to gauge the exact value of my film due to the nature of my work as an art piece, however, my film may be valuable in helping people (regardless of age or nationality) understand themselves better by looking inside themselves and their own memories in depth, and helping them get over their own demons and barriers that prevent them from being the best versions of themselves.